The transformation from value determination to value realization: the logical dilemma of the Okishio theorem - Shengsheng Wang; Bangxi Li; Shan Gu (China Political Economy, 2021)
Purpose – Different from Marx's analysis of the dialectical relationship between the production and realization of surplus value, the Okishio theorem only shows one aspect of the contradictory movement of the total social capital, that is, the reverse effect of the realization of surplus value on the production of surplus value. Design/methodology/approach – The production of surplus value and the realization of surplus value are simplified into one process. This simplification eliminates the contradiction between the production and realization of surplus value, and the antagonistic contradiction between accumulation and consumption and the antagonistic production-distribution relationship in capitalist society are naturally covered up. Findings – Therefore, it cannot explain the actual expansion way of the falling general rate of profit as the historical development law of capitalism. Nevertheless, it should be noted that the Okishio theorem places the analysis of the general rate of profit back into the social reproduction model with department equilibrium, which points out the significance of wage income to the realization of surplus value and outlines the macro mechanism of the realization of surplus value reacting to the production of surplus value. It also strongly promotes the research progress of the law that the profit rate tends to decline. Originality/value – The mistake of the Okishio theorem is that the exchange process in the labor market forms the real wage rate. It determines the production price of wage goods, which thereby determines that the production price of capital goods and general rate of profit, the production of surplus value and realization of surplus value are simplified into the same process, and only the value that can be realized is the real value.